STUDY OF EXCAVATION SLOPE STABILITY WITH GROUND ANCHOR ON TOLL ROADS IN NORTH SULAWESI PROVINCE - Rizki Sakinah, Kiki
The conditions of the construction development path are often not always in the lowlands but can also be in the highlands, which require good slope stability planning. Soil conditions and high levels of earthquake susceptibility need to be properly identified for construction planning in highland locations to accommodate slope failures or soil instability. Slope stability can be influenced by several factors that can cause landslides, such as the slope profile of the slope, increased water pressure due to rain, seepage, or the appearance of surface water, and the presence of vibrations caused by earthquake loads. Uncertainty about the location of the groundwater table greatly affects the stability of the slopes in the future. This study aims to determine the effect of the groundwater table and the application of prestress force to the anchors on the stability of the excavation slope. Research will be carried out by PLAXIS 2D software. First, modeling the stability analysis of the unreinforced slopes is carried out, and the calculations are carried out with gradual excavation. The results obtained indicate that the excavation slope is not safe, with a safety factor value of 1.23. Next, modeling the stability analysis of the excavation slope with ground anchors using a prestress force of 200 kN The results obtained indicate that the excavation slopes are not safe with safety factors in short-term, long-term conditions, and earthquake loads, respectively, namely 1.43, 1.1, and 1.03. The tensile force that occurs in the anchor has the potential to fail to pull out in the analysis of long-term conditions and earthquake loads because it does not meet the allowable tensile strength of the tendons. The settlement that occurs at the foot of SUTET also does not meet the requirements for settlement of frame tower foundations of less than 5 cm. In modeling the stability analysis of excavation slopes by varying the groundwater level at depths of 5 m, 10 m, 15 m, 20 m, 30 m, and 44 m and varying the prestress force of 100 kN, 200 kN, 300 kN, 400 kN, and 500 kN, the results show that, in general, the ground anchor design used does not work effectively. This happens because the bonded length is in the slip plane for global stability.